OP0126 LYMPHOMA ARISING AT THE TIME OF DIAGNOSIS OF PRIMARY SJÖGREN SYNDROME: A HIGHLY-ACTIVE SYSTEMIC SUBSET OF THE DISEASE - Soledad Retamozo; Nihan Acar‐Denizli; Wan‐Fai Ng; Antónia Szántó; Astrid Rasmussen; Raphaèle Séror; LI Xiaomei; Chiara Baldini; Jacques-Éric Gottenberg; Pulukool Sandhya; Luca Quartuccio; Roberta Priori; et al. (2019)
Objectives To analyse the phenotype of patients with primary Sjogren syndrome (SjS) in whom a lymphoproliferative disease is diagnosed concomitantly. Methods By January 2019, The Big Data Sjögren Project included 11,420 consecutive patients with primary SjS recruited from 24 countries of the five continents. Results 117 (1%) patients were diagnosed with lymphoma and primary SjS synchronously. Age-gender adjusted multivariate analysis identified the following features associated with lymphoma (OR; CI95%): male gender (4.61; 2.88-7.18), White ethnicity (3.51; 1.78-7.91), abnormal oral tests (3.4; 1.38-10.88), positive biopsy (3.2; 1.3-10.17), positive RF (2.27; 1.48-3.53), hypocomplementemia (3.39; 2.06-5.54), and cryoglobulins (4.74; 2.57-8.38). Activity (score > 1) in the constitutional (2.97; 1.86-4.62), glandular (3.11; 2.1-4.57), cutaneous (2.17; 1.28-3.52), peripheral nerve (2.56; 1.4-4.41) and hematological (2.49; 1.64-3.75) ESSDAI domains was associated with lymphoma (frequencies summarized in the Figure). Conclusion Patients diagnosed concomitantly with primary SjS and lymphoma have a very specific, highly-active phenotype (men, White, severe oral involvement, cryoglobulinemic-related immunological markers, and high systemic activity). Disclosure of Interests:  Soledad Retamozo: None declared, Nihan Acar-Denizli: None declared, Wan Fai Ng: None declared, Antónia Szántó: None declared, Astrid Rasmussen: None declared, Raphaèle Seror Grant/research support from: Pfizer, Consultant for: Bristol-Myers Squibb, Pfizer, Amgen, Eli Lilly, Roche, Celgene, GlaxoSmithKline, MedImmune, Xiaomei Li: None declared, Chiara Baldini: None declared, Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Lilly, Pfizer, Sanofi-Genzyme, UCB Pharma, Consultant for: Bristol-Myers Squibb, Eli Lilly, UCB, Sanofi-Genzyme, Pfizer, Pulukool Sandhya: None declared, Luca Quartuccio: None declared, Roberta Priori: None declared, Gabriela Hernandez-Molina: None declared, Berkan Armagan: None declared, Aike A. Kruize: None declared, Seung-Ki Kwok: None declared, Marika Kvarnstrom: None declared, Sonja Praprotnik: None declared, Damien Sene: None declared, Roser Solans-Laqué: None declared, Maureen Rischmueller Consultant for: Abbvie, Bristol-Meyer-Squibb, Celgene, Glaxo Smith Kline, Hospira, Janssen Cilag, MSD, Novartis, Pfizer, Roche, Sanofi, UCB, Thomas Mandl: None declared, Yasunori Suzuki: None declared, David Isenberg: None declared, Valeria Valim: None declared, Agata Sebastian: None declared, Gunnel Nordmark: None declared, Hendrika Bootsma: None declared, Hideki Nakamura: None declared, Roberto Giacomelli Grant/research support from: Pfizer, Actelion, Speakers bureau: Actelion, Bristol-Myers Squibb, Merck Sharp & Dohme, Abbvie, Pfizer, Sobi, Roche, Valerie Devauchelle-Pensec Grant/research support from: Roche-Chugai, Speakers bureau: MSD, BMS, UCB, Roche, Benedikt Hofauer Consultant for: Consultant for Galvani Bioelectronics for the area of sleep disorders., Michele Bombardieri Grant/research support from: Celgene, Consultant for: Medimmune, Virginia Fernandes Moça Trevisani: None declared, Daniel Hammenfors: None declared, Sandra Pasoto: None declared, Tamer A Gheita: None declared, Fabiola Atzeni: None declared, Jacques Morel: None declared, Cristina Vollenveider: None declared, Sandra Consani-Fernández: None declared, Xavier Mariette Grant/research support from: Servier, Consultant for: AstraZeneca, Bristol-Myers Squibb, GlaxoSmithKline, Janssen, Pfizer, UCB Pharma, Manuel Ramos-Casals: None declared, Pilar Brito-Zerón: None declared, Elena Bartoloni Bocci: None declared